First record of Mahanarva spectabilis (Distant) (Hemiptera: Cercopidae) in the state of Acre, Brazil - Santos, Rodrigo Souza; Andrade, Carlos Mauricio Soares de; Carvalho, Gervásio Silva (EntomoBrasilis, 2021)
Spittlebugs are among the main insect pests of forage grasses in Brazil. In February 2021, a spittlebug infestation was verified in Xaraés palisadegrass (Brachiaria brizantha cv. Xaraés) in the municipality of Senador Guiomard, Acre state, Brazil. The specimens were captured with an entomological sweep net and identified as Notozulia entreriana (Berg) and Mahanarva spectabilis (Distant) (Hemiptera: Cercopidae). Notozulia entreriana is frequently captured in studies with spittlebugs in Acre state, though this is the first record of M. spectabilis in the state. This new record expands the species known geographical distribution in Brazil and the number of species of Mahanarva occurring in Acre state.